Gender, Ethnicity, Family Socio-Economics, and Grit (A Islamic Higher Education Students Context) - Juhaidi, Ahmad (International Journal of Multidisciplinary Sciences, 2024)
Grit is a non-cognitive factor that is crucial in achieving success in education. The purpose of this study is to verify differences in grit and its two aspects (consistency and perseverance) between gender and ethnicity in Islamic higher education students. The study also verified the correlation between parents' education levels, family economic background, grit total, consistency of interest, and perseverance of effort. This research is field research with a quantitative approach. The participants amounted to 267 students of Antasari State Islamic University. Convenience techniques and snowballing sampling determined participants. Researchers used descriptive statistics, the Mann-Whitney U, Kruskal Wallis H, and Spearman's Rank Correlation test to analyze the data. The results showed no significant differences in total grit levels and its aspects between gender and ethnicity (Sig.>0.005). Dayak ethnic minorities are more persistent and grittier than the majority ethnicity, Banjar, but not significant. Parental education does not correlate with total grit and both aspects. The influence of gender, ethnicity, and socio-economic background on grit is also determined by the type of education students attend.